A non-inferiority trial comparing two recombinant vaccines (Hepa-B vs. Engerix-B) for hepatitis B among adults in Dhaka, Bangladesh. Issue 43 (15th October 2021) - Chowdhury, Fahima; Akter, Afroza; Rahman Bhuiyan, Taufiqur; Tauheed, Imam; Ahmed, Tasnuva; Ahmmed, Faisal; Ahmed, Faez; Karim, Mahbubul; Mainul Ahasan, Mohammad; Rahman Mia, Masudur; Mohammad Ibna Masud, Mir; Wahab Khan, Abdul; et al.
Abstract: Worldwide Hepatitis B is known as one of the imperative causes of mortality and morbidity as well as occupational health hazard among health workers. Bangladesh is intermediate endemic country for Hepatitis B infection for which the government has introduced hepatitis B vaccination into the Expanded Programme on Immunization (EPI) nationwide since 2009 for new born children. However, the people who were born before 2009, was dependent on imported hepatitis B vaccine as there was no locally manufactured hepatitis B vaccine in Bangladesh. Hence, we conducted a randomized observer blinded non-inferiority clinical trial to assess the immunogenicity and safety of the locally manufactured Hepa-B vaccine in comparison with World Health Organization prequalified Engerix-B vaccine. Total 158 eligible adult participants were enrolled in this study with mean age of 30 and 29 years old in Hepa-B and Engerix-B groups, respectively. Both the vaccines were administered intramuscularly at 0, 1 and 6 months schedule. Baseline and post vaccination anti-HBs titers were measure at different time points. Seroconversion rate post three doses of Hepa-B vaccine was 98.67% similar to the comparator Engerix-B vaccine which was 100%. The geometric mean test ratios of both vaccines at all analysis time points were found > 0.5 predefined non-inferiority margin. Soreness at the injection site was the most common symptom for both the vaccines which resolved without any complication. No serious adverse event was reported throughout the study period. These results suggest that locally manufactured hepatitis B vaccine 'Hepa-B' vaccine is non-inferior to the well-known licensed 'Engerix-B' vaccine. ClinicalTrials.gov NCT03627507.